2018
DOI: 10.12783/dtetr/iccere2017/18334
|View full text |Cite
|
Sign up to set email alerts
|

Model Test Study on Dredge Slurry Vacuum Preloading

Abstract: Dredge materials with the water content more than 80% have been used for land reclamation in Tianjin, China. The dredge is transferred by pipeline to the reclamation place and then strengthened with the vacuum preloading technique. It has been found that with the thickness of the filled dredge layer becomes larger and larger, the quality of soil improvement is not as good as expected. Field investigation shows that after vacuum preloading the vane test strength can reach 50kPa at the ground surface, but decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Environmentally friendly materials have been gradually replacing plastic drainage boards for treating dredged sediment in recent years (e.g., Liang et al,2016;Tang et al,2020;Xu et al,2022). Natural pine wood can be used as a drainage body in combination with vacuum preloading to treat dredged sediment (Jian, 2022). It has been demonstrated that the inherent stiffness of pine wood can effectively reduce the bending degree in the drainage body, thereby improving vacuum transmission e ciency.…”
Section: Introductionmentioning
confidence: 99%
“…Environmentally friendly materials have been gradually replacing plastic drainage boards for treating dredged sediment in recent years (e.g., Liang et al,2016;Tang et al,2020;Xu et al,2022). Natural pine wood can be used as a drainage body in combination with vacuum preloading to treat dredged sediment (Jian, 2022). It has been demonstrated that the inherent stiffness of pine wood can effectively reduce the bending degree in the drainage body, thereby improving vacuum transmission e ciency.…”
Section: Introductionmentioning
confidence: 99%